Upaya Pengembangan Obyek Wisata Bunga dalam Pembangunan Ekonomi Lokal (Studi Kasus di Desa Sidomulyo Kota Batu) - Yoehansyah, Alief (Jurnal Administrasi Publik, 2013)
Abstract The Research on development efforts of the flowers tourism of the local economy development (case studies in Sidomulyo Village Batu City). The descriptive nature of the research with qualitative approaches. It is meant that benefits of development can be felt directly either from the government or the community through increasing revenue and job creation as well as establishing an independent and creative community. The focus of this research, the first development of Department of tourism efforts of the flowers tourism in the Sidomulyo Village Batu City; second The impact of arising from the development of flowers tourism in Sidomulyo Village towards the development of the local economy in Sidomulyo Village Batu City; third enabling and inhibiting factors in developing flowers tourism in sidomulyo village towards the development of the local economy in Sidomulyo Village Batu City. From the research results above, it can be noted that the role of Government in the development of tourism as a coordinator and facilitator to involve communities directly could be said to be doing well by implementing local economic development. The villagers are given the freedom to innovate in managing and accentuates potency that is known to the wider community as a new tourist destination in the Batu City.   Keyword: Development Efforts, Flowers Tourism, Local Economic Development Abstrak Penelitian yang dibahas adalah mengenai upaya pengembangan obyek wisata bunga dalam pembangunan ekonomi lokal (studi kasus di Desa Sidomulyo Kota Batu). Hal ini bertujuan  agar manfaat pembangunan dapat dirasakan langsung baik dari sisi pemerintah maupun masyarakat yaitu melalui peningkatan pendapatan dan penciptaan lapangan pekerjaan serta membentuk masyarakat yang mandiri dan kreatif. Fokus penelitian ini, pertama upaya Dinas Pariwisata dalam pengembangan obyek wisata bunga di Desa Sidomulyo Kota Batu; kedua,  dampak  pengembangan obyek wisata bunga  dalam pembangunan ekonomi lokal di Desa Sidomulyo Kota Batu; ketiga, faktor pendukung dan penghambat dalam mengembangkan obyek wisata bunga terhadap pembangunan ekonomi lokal di Desa Sidomulyo Kota Batu. Dari hasil penelitian di atas, dapat diketahui bahwa peran pemerintah dalam pengembangan obyek wisata sebagai koordinator dan fasilitator dengan melibatkan masyarakat langsung dapat dikatakan berjalan dengan baik dengan menerapkan pembangunan ekonomi lokal. Masyarakat desa diberikan kebebasan untuk berinovasi dalam mengelola dan menonjolkan potensi yang dimiliki agar dikenal masyarakat luas sebagai daerah tujuan wisata yang baru di Kota Batu.   Kata Kunci: Upaya Pengembangan, Obyek Wisata Bunga, Pembangunan Ekonomi Lokal